Exploiting the molecular subtypes and genetic landscape in pancreatic cancer: the quest to find effective drugs - Elebo, Nnenna; Abdel-Shafy, Ebtesam A.; Cacciatore, Stefano; Nweke, Ekene Emmanuel (Frontiers in Genetics, 2023)
Pancreatic Ductal Adenocarcinoma (PDAC) is a very lethal disease that typically presents at an advanced stage and is non-compliant with most treatments. Recent technologies have helped delineate associated molecular subtypes and genetic variations yielding important insights into the pathophysiology of this disease and having implications for the identification of new therapeutic targets. Drug repurposing has been evaluated as a new paradigm in oncology to accelerate the application of approved or failed target-specific molecules for the treatment of cancer patients. This review focuses on the impact of molecular subtypes on key genomic alterations in PDAC, and the progress made thus far. Importantly, these alterations are discussed in light of the potential role of drug repurposing in PDAC.